Characterization of ZnO nanobelt-based gas sensor for H2, NO2, and hydrocarbon sensing - Sadek A.Z. (2014)
A conductometric H2, NO2, and hydrocarbon gas sensor based on single-crystalline zinc oxide (ZnO) nanobelts has been developed. The nanobelt sensitive layer was deposited using a radio frequency (RF) magnetron sputterer. The microcharacterization study reveals that the nanobelts have a single crystal hexagonal structure with average thickness and width of about 10 and 50 nm, respectively. The sensor was exposed to H2, NO2 and propene gases at operating temperatures between 150°C and 450°C. The study showed that optimum operating temperatures for the sensor are in the range of 300°C-400°C for H2, 300°C-350°C for NO 2, and 350°C-420°C for propene sensing. © 2007 IEEE.